Coexistence of rhombohedral and orthorhombic phases in ultrathin BiFeO3 films driven by interfacial oxygen octahedral coupling. (15th February 2018) - Han, M.J.; Wang, Y.J.; Ma, D.S.; Zhu, Y.L.; Tang, Y.L.; Liu, Y.; Zhang, N.B.; Ma, J.Y.; Ma, X.L.
Abstract: Coexistence of two phases creates a morphotropic phase boundary in perovskite oxides, which can provide large piezoelectric response, generating it a well suited system for probe-based memories and actuator applications. The coexistence of two phases in thin films is proposed to be induced by epitaxial constraints from substrates or chemical compositional modifications by substitution. In this work, we found a new formation mechanism of two-phase coexistence driven by interfacial oxygen octahedral coupling (OOC) in oxide heterostructures. We fabricated a series of BiFeO3 (BFO) ultrathin films on various orthorhombic substrates exerting from tensile to compressive strains by Pulsed Laser Deposition (PLD) techniques. Aberration-corrected transmission electron microscopy demonstrates that the lattice rotation and oxygen octahedral rotation (OOR) patterns transfer from these substrates to BFO films in about 3 unit cells while an orthorhombic ( Pnma ) phase forms at the interface due to OOC. This Pnma phase is non-polar, which differs from polar phases of Ima2 or Pmc2 1 when a large tensile strain is imposed onto BFO. First-principles calculations reproduce these experimental results perfectly. This phase transition occurs when BFO films are under both tensile and compressive strains suggesting that OOC alone can induce phase transition in ultrathin BFO films. Such coexistence of two phases may have many potential applications in the field of electronics, such as ferroelectric sensors and actuators. Graphical abstract: Image 1